Chondrotoxicity of Local Anesthetics: Liposomal Bupivacaine Is Less Chondrotoxic than Standard Bupivacaine - Travis Farmer; S. Craig Morris; Robert Quigley; Nirav H. Amin; Montri D. Wongworawat; Hasan M. Syed (Advances in Pharmacological and Pharmaceutical Sciences)
Objective. The purpose of this study is to determine whether (1) liposomal bupivacaine is chondrotoxic; (2) the chondrotoxicity of liposomal bupivacaine differs from standard bupivacaine; and (3) chondrotoxic effects are time dependent. Materials and Methods. We obtained 72 10 mm articular cartilage plugs from 12 fresh bovine distal femoral knee joints and exposed them to either saline, 0.5% bupivacaine, or liposomal bupivacaine for either 30 or 90 minutes. Twenty-four hours after treatment, chondrocyte viability was measured with the use of a fluorescent live/dead assay. An ANOVA test of variance was performed followed by a Holm–Sidak test to make pairwise comparisons across conditions. Student’s t-test was used to compare means. Results. Percent viability of cells exposed to liposomal bupivacaine for 30 minutes was less versus saline control (53.9% ± 21.5% vs. 73.7 ± 18.4%, p=0.035), and this remained significant at 90 minutes (49.1% ± 20.3% vs. 67.2% ± 25.6%, p<0.001). Liposomal bupivacaine had less chondrotoxic effects when compared with bupivacaine after 90 minutes, with greater viability (49.1% ± 20.3% vs. 21.4% ± 14.0%, p=0.003). Chondrotoxicity was found to be time dependent within the bupivacaine group (percent viability at 30 min: 45.5 ± 18.2%, 90 min: 21.4 ± 14.0%, p=0.001); however, liposomal bupivacaine did not demonstrate a significant time-dependent chondrotoxic relationship (p=0.583). Conclusions. Bupivacaine and liposomal bupivacaine are both toxic to chondrocytes. Liposomal bupivacaine is less chondrotoxic than standard bupivacaine and does not demonstrate a time-dependent toxicity.